THE EFFECT OF MICROENCAPSULATION METHOD OF THIN-LAYER DRYING OF Dioscorea hispida Dennts. TUBERS ON THE STABILITY AND EFFECTIVENESS OF BIOHERBICIDES - Putri, Windi Egidya; Asni; Fatima, Wa Ode (Universitas Veteran Bangun Nusantara, 2026)
This study was conducted to investigate the microencapsulation properties of Dioscorea hispida Dennst. tuber extract processed using the thin layer drying method and to evaluate the effectiveness of the resulting microencapsulated product as a bioherbicide against broadleaf weeds. The extract was prepared at three concentration levels (20%, 30%, and 40%) with three replications, and each extract was mixed with maltodextrin and Tween 80 as coating materials prior to the drying process to produce microencapsulated powder. The analysis results showed that the microcapsules exhibited a spherical shape, good stability, and high encapsulation efficiency. SEM observations revealed the presence of two distinct layers, indicating that the active compounds were well entrapped within the coating matrix. Toxicity testing (%) was conducted through visual observation using a scoring method. Phytotoxicity tests on Ageratum conyzoides showed the highest toxicity symptoms at a concentration of 40%, with a score of 20%, characterized by chlorosis, leaf drop, and physiological disturbances. Ageratum conyzoides exhibited a phytotoxicity level of 20%. Overall, these results confirm that microencapsulated Dioscorea hispida Dennst. extract has strong potential as a natural bioherbicide for suppressing the growth of broadleaf weeds. Keywords: Bioherbicide; Dioscorea hispida Dennts; Microencapsulation; Phytotoxicity; Thin layer drying.